Construction and assessment of Maqasid al-Shari’ah - society’s perception index (MS-SPI) - Osman, Zurul Aisya; Muhamad, Barudin; Abdullah, Naziruddin; Ali, Siti Mariam (2023)
This study was carried out to construct an indicator that assess social wellbeing based on the society’s perception within the context of Maqasid al-Shari’ah. Commonly, this is done at the institutional level, hence policy direction may have overlooked the individual condition in the society. Accordingly, the main objective of this study is twofold. First is to construct indicators based on Maqasid al-Shariah framework utilizing five (5) elements of dharuriyyah and to aggregate the constructs into forming novel Maqasid al-Shari’ah-Society’s Perception Index (MS-SPI). Second is to assess the five (5) constructs and the MS-SPI. This study is quantitative in nature and provide empirical assessment on a composite indicator. It employs secondary data from Wave 5 and 6 in the World Values Survey (WVS) within Malaysian setting. Furthermore, this study incorporates the stepwise index construction procedure to engender the five (5) constructs and the MS-SPI. Results indicate that the offspring construct have the highest score while the wealth construct has the lowest score. In addition, the MS-SPI value exhibits that the society’s perception of Maqasid al-Shari’ah achievement is only slightly above the average range. The methodology and novel technique for index construction in this study provides new way of integrating multidimensional social data into a composite indicator. It also emphasizes the social wellbeing as perceived at the societal rather than commonly viewed institutional level. Practical contributions in this study are attributed from the application of the MS-SPI in assessing level of social wellbeing based on the society’s perception within the context of Maqasid al-Shari’ah. Policy directions should focus more on the least performing element in order to improve the whole system. The paper provides original proxy data and stepwise index construction procedure to build the constructs and subsequently composite indicator i.e. MS-SPI.